Developing AI-Enhanced Animated Educational Media for Pancasila Character Education: A Comprehensive Needs Analysis in Indonesian Junior High Schools - Alvionita, Rini; Safitri, Erna Retna; Chotimah, Umi (Papanda Publisher, 2025)
Character education has become a critical imperative in 21st-century learning, particularly at the junior high school level where students undergo pivotal developmental phases. Despite the potential of artificial intelligence (AI) and animation technologies to enhance character education, significant implementation challenges persist in Indonesian educational contexts, with limited research examining stakeholder needs for AI-based learning media incorporating Pancasila Student Profile characteristics. This descriptive quantitative study within a research and development framework analyzed needs for developing AI-based animated video learning media at SMP Negeri 6 Sungai Keruh. Data were collected through structured questionnaires administered to 28 seventh-grade students and 8 teachers, examining pedagogical, technical, cognitive, aesthetic, and evaluative dimensions. Descriptive statistical analysis was employed to identify dominant patterns and stakeholder preferences using Guttman scaling principles. Student analysis revealed strong preferences for audiovisual learning modalities (85.5% enhanced information absorption through visual-audio combinations) and aesthetic design elements (85.5% increased motivation through attractive design). Technical accessibility showed 78.5% adequate device access, while 80.0% recognized evaluation mechanisms' importance. Teacher analysis demonstrated pedagogical readiness with 85.5% recognizing animation effectiveness and universal technical infrastructure support (100.0% internet connectivity), though 64.5% required additional professional development for optimal implementation. Findings demonstrate substantial stakeholder readiness for AI-based animated learning media development while identifying specific support areas. Results align with theoretical frameworks supporting animation's cognitive processing advantages and provide empirical evidence extending existing Pancasila Student Profile-based media research from elementary to secondary contexts. The convergence of theoretical frameworks, empirical evidence, and stakeholder needs establishes robust foundation for subsequent development phases, contributing to advancing character education through innovative technological integration.